Kajian ke atas petikan dan kiasan dalam prosa Buddha Mahua, 1985-2010 / Lew Ya Ling - Lew , Ya Ling (2017)
Mahua Buddhist prose is written in Chinese and focuses on the theme of Buddhism. Readers often have the impression that Mahua Buddhist prose only uses literature technique to present the teachings of Buddhism. “Explanation of teachings” in Buddhist prose; probably are not only focus that observed and appreciated by the writer and the reader. They may be more concerned with the sharing of religious experience and feelings. Therefore, this study aims to explore the lyric characteristics found in the Mahua Buddhist prose through quoting literature. Since quoting technique is usually used to prove own views, readers may ignore the other functions of quoting. Therefore, this study also aims to change perceptions about quoting function that is not limited to evidence only. The scope of this study focuses on Mahua Buddhist prose anthology published between 1985 and 2010, analyze prose anthology of Ven Jicheng, Huang Xueming, He Naijian, Guo Lianhua, Su Qingqiang, He Jin, Ye Qiuhong and others. The methodology used is Chinese Lyrical Tradition, and also the use of literary Quotations and Allusions from Intertextuality. This study is divided into seven chapters, where by chapter one is the introduction. Chapter two is about the background of Mahua Buddhist prose. The third chapter, entitled “Humanism Lyric Element in The Use of Quotations and Allusions from Buddhist Scriptures” examines the reasons of the writers choosing quoting from certain Buddhist scriptures, observing the ways of quoting, explaining their views of Buddha image in the prose. Chapter four, “Pursuit of Religious Realm in The Use of Quotations and Allusions from the Book of Zen” analyzes the religious realm in Mahua Buddhism. Next it examines the most widely used of the Zen book in Mahua Buddhist prose and its cultural implications, and finally examines the differences between the use of quotations and allusions‟ methods of Ven Jicheng and Huang Xueming by comparison. Chapter five, entitled “The Use of Quotations and Allusions from Classical Chinese Poetry and Solitary Feeling in Lyric” analyses the condition of the quoting from classical Chinese poetry, discussing the reasons authors quoting from classical Chinese poetry. The solitary feeling will be explored through the analysis of the imagery in the prose, cultural implications are also studied. Chapter six “Ethical Aesthetic: The Meaning of The Use of Quotations and Allusions from the Book of Confucianism and Taoism”, is to examine the factors of the existence of integrated thinking of Confucianism, Taoism and Buddhism in Mahua Buddhist prose, the ways of quoting, reasons the authors use quotations and allusions from the book of Confucianism and Taoism in Mahua Buddhism prose. Each chapter responds to the four dimensions of lyrical in Mahua Buddhist prose: time and space based on humanism, ideal for religious realm based on reality, the hidden solitary feeling and aesthetic pursuit. This study shows that Buddhist prose is not just limited to the propagation of Buddhism; it is open to wider interpretation. In addition, quoting and allusion techniques can also achieve the unexpected, encouraging the aesthetic appearance and the deeper implications.